Actitud y práctica de medidas preventivas sobre COVID 19 en trabajadores del mercado Oscar Iván de Iquitos 2021 - Torres Ramirez, Angela Celeste (2021)
The objective is to determine the relationship between the attitude and the practice of preventive measures on COVID-19 in workers aged 18 to 70 years of both sexes at the Oscar Iván Market in Iquitos 2021. The study was Quantitative with a non-experimental, correlational and cross-sectional design, the population was made up of 128 workers from the Oscar Iván Market in the city of Iquitos. The techniques used were the interview and observation, the instruments were the Attitudes Scale towards COVID-19 (Validity 93.0% and Reliability 90.7%), and the COVID-19 preventive measures observation guide (Validity 94.4% and Reliability 92.6%). It was found 78.9% workers had a negative attitude towards COVID-19 while 21.1% had a positive attitude; In the practice of preventive measures against COVID-19, 76.6% had inadequate practice and 23.4% had adequate practice, when applying the Chi Square, a statistically significant result was obtained X2 = 5.709 and p = 0.017 < 0.05. It is concluded that there is a significant statistical relationship between the attitude and the practice of preventive measures on COVID-19 in workers between the ages of 18 and 70 of both sexes at the Oscar Iván de Iquitos 2021 Market.